Intervenção precoce na infância: revisão de literatura no contexto brasileiro - Silva, Maria Izabel Alves Felix da (2022)
The Intervention is descriptive of practices to promote learning and with disabilities or in conditions of development of a child development project. In the past it was already called, as infantile, early stimulation of infantile stimulation. This study is justified by the need to bring national scientific contributions to the paradigm shift of Early Childhood Intervention (ECI) practices and the adoption of family-centered practices. It aims to analyse how Brazilian productions of theses and dissertations have contributed to Early Intervention in Childhood, in terms of methodology, approaches and ways of including the family. This study as a quantitative and qualitative methodology the state of knowledge of the art, which allows a selection of systematization model selection, knowing a production of knowledge in a certain period. The mapping of theses and dissertations was carried out on the platform of the Brazilian Digital Library of Theses and Dissertations - BDTD IBICT and on the CAPES Theses and Dissertations Catalog database, with the survey of titles, abstracts and complete works of conclusion of the Programs of Academic Master's, Professional Master's and Doctorate, in the Great Area of Health (Occupational Therapy, Physiotherapy, Speech Therapy, Psychology, Health Sciences), Nursing and Education (Special Education). The survey took place in the intervention period between 197 words relevant to 2020 and the identification identified to, which as differentiation97 took place in the intervention period: early; early stimulation; services; childhood; kid. The elements of analysis listed were keywords; covered areas; institutions, states and regions; year of publication; nature of research; participants and research topics. As categories they deal with the themes: it has been named in Brazil on early stimulation and early intervention; survey on the Brazilian historical and political evolution of early intervention actions; of how the services described as early intervention practices and how the description of the family's participation in the services is carried out and a survey of how therapists have contributed to studies on Early intervention. The research will provide a systematic overview and dissertations of recent research in Brazil, analysing the work carried out for the advancement of public research and in the first years of public research. An analysis of studies has shown that ECI practices in Brazil are very far from the principles of intersectionality and increasing the competences of families to deal with children's development issues. The need to bring scientific and practical contributions to a paradigm shift in Early Childhood Intervention practices is identified. It was also found that the model developed and the children with alterations appear more related to rehabilitation and intervention clinic. Finally, considering, if it is a study of overdue investigation, the results of a study on a panorama for future studies that need to be studied, to indicate the development of new interrelated research. Childhood and public policies in Brazil.